The influence of size and content of Libyan limestone particles on the mechanical properties of high-density of polyethylene (Sebha University Conference Proceedings, 2025)
This study investigated the effect of size and content of Libyan limestone (calcium carbonate (CaCO3)) particles on mechanical properties of high-density polyethylene (HDPE). CaCO3 rocks were crushed and ground into nano and coarse sizes using a hammer mill and a centrifugation ball mill. HDPR/CaCO3 Composites containing 10, 20 and 30% CaCO3 prepared using polyethylene glycol (PEG) as a coupling agent. The mechanical properties including; impact strength, tensile strength, young’s modulus and Shore hardness was evaluated. The correlation between mechanical properties and the amount and size of CaCO3 was also investigated. X-ray diffraction (XPD) results illustrated that the average sizes of the coarse and fine CaCO3 particles were 74 nm and 1 nm, respectively. The results that the impact strength was decreased significantly with the addition and increasing the amount of CaCO3. On the other hand, the tensile strength was increased with increasing the content of CaCO3 up to 20%, and then decreased. Young’s modulus and Shore hardness were increased with the increasing the CaCO3 content. As expected, fine (nano) CaCO3 composites demonstrated better overall mechanical properties than composites made with coarse CaCO3. The results showed also a strong positive relationship between size and content of CaCO3 with most of the studied mechanical properties. Most importantly, Libyan CaCO3 showed to be an excellent reinforcing material for polyethylene since it enhanced its mechanical properties and has the potential to reduce the production cost of these materials.